(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2022)
Solidly based on sources and documents unpublished in the Western panorama, the article reconstructs an episode of rare interest in the history of Chinese and world performing arts, based on a process of translation between different mediums and languages: the research carried out from 1977 on the frescoes in the Dunhuang caves (4th-14th century AD) - context in which the first pioneering experiments in written notation of dance emerged - led to the creation of the dance show theatrical Rain of Flowers on the Silk Road (1979), and was later translated into a dance film in 1982, in a TV show in 2008 and in a digital video gone viral in 2021. This process corresponds with a transition from the two-dimensionality of the static positions of painting to the four-dimensionality of the moving bodies of the dancers, up to the application of cinematographic language to transcribe the choreography on screen, and to the potential of digital dissemination allowed by social media, and motion capture. The depictions of mythological creatures, dancers and musicians, painted from the 4th to the 14th century AD on the walls of the Mogao caves almost as if they were an archive of choreutic poses, were used to reconstruct the choreography of ancient traditional dances. The concept of archive could also be applied to the film translation phase, which allowed the permanence and transmission of that choreography, and its current digital counterpart linked to the social media environment.